2014
DOI: 10.1177/1357633x14528443
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of telepractice delivery for teaching listening and spoken language to children with hearing loss

Abstract: Telemedicine ("telepractice") allows improved access to specialised early intervention services such as Auditory-Verbal Therapy (AVT) for children with hearing loss. We investigated the effectiveness of a tele-AVT programme (eAVT) in the spoken language development of a group of young children with hearing loss. In a retrospective study we compared the language outcomes of children with bilateral hearing loss receiving eAVT with a control group who received therapy In Person. Seven children in each group (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 9 publications
(13 reference statements)
4
34
0
3
Order By: Relevance
“…6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment. 8,22,30 Five studies (19%) reported a pre-test / post-test design, 9,11,16,26,28 while three (11%) reported method-comparison studies. 14,20,24 Qualitative designs were …”
Section: Study Purposementioning
confidence: 96%
See 2 more Smart Citations
“…6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment. 8,22,30 Five studies (19%) reported a pre-test / post-test design, 9,11,16,26,28 while three (11%) reported method-comparison studies. 14,20,24 Qualitative designs were …”
Section: Study Purposementioning
confidence: 96%
“…7,9,10,12,13,19,26 and clinical education was described in six (22%) articles. 6, 27-31 Speech and language pathology was described in four (15%) articles, 8,18,24,25 with critical illness 5, 17, 21 and mental health 11, 15, 16 both represented in three (11%) articles each. Pathology 14, 23 was described in two (7%) articles.…”
Section: Clinical Application Areasmentioning
confidence: 98%
See 1 more Smart Citation
“…Behl, Callow-Heusser, and White (2013) conducted a randomized control study of 27 families of infants and toddlers with hearing loss and evaluated pre- and post-test measurements on child and family outcomes, family and provider satisfaction, and cost. Most recently, Constantinescu et al (2014) provided auditory-verbal therapy (AVT) via telepractice to seven young children (mean age 2:4 years) with hearing loss. The children’s outcomes using the Preschool Language Scale-4 (PLS-4) were compared with another group of seven age equivalent children with hearing loss who received AVT in the traditional in-person method.…”
mentioning
confidence: 99%
“…A teleconsulta pode ser desempenhada de três diferentes formas (Krumm, 2007, Ferrari et al, 2010: Pesquisas demonstram a eficácia do uso da teleconsulta para o diagnóstico audiológico (Givens, Elangovan, 2003, Choi et al, 2007, Krumm et al, 2007, Andersson et al, 2003, o tratamento do zumbido (Kaldo et al, 2008), a adaptação de Aparelho de Amplificação Sonora Individual (AASI) (Ferrari, 2006, Ferrari, Bernardez-Braga, 2009, Campos, Ferrari, 2012 e o processo terapêutico (Constantinescu 2012, Constantinescu et al, 2014. (Brasil, 1999) e em estudos internacionais (Moret, Costa, 2015).…”
Section: Determinação Dos Níveis De Estimulação Elétricaunclassified